Estimating the difference of agriculture productivity in ASIAN regions - Hira, Swati; Bai, Anita (International Journal of Engineering and Technology, 2018)
Agriculture is the major sector in the economy of Asia. The aim of this paper is to identify the importance of agriculture in Asia continent. In this paper, we evaluate differences between and within regions of Asia (Eastern-Asia, South-Central Asia, South-East Asia, and Western Asia and Middle Asia) and their countries. We used five agriculture parameters (Agriculture Land, Cereal production, Machinery, Tractors, Cereal yield, Land under cereal production) which widely represent agriculture productivity of Asia. The means of all Asian regions and its countries are identically similar is considered as a hypothesis for agriculture parameters. We use One-way ANOVA (analysis of variance) technique for analysis. Further, Asian regions and countries are estimated to test the differences of the means between and within regions and countries of each Asian region. The results show that each Asian region and their countries are having different agriculture productivity for agriculture parameters.Â Â